100. 177Lu-PSMA molecular radiotherapy: Strategy to reduce organ at risks uptake. (December 2018) - Belli, M.L.; Mezzenga, E.; D'Errico, V.; Bianchini, D.; Severi, S.; Tardelli, E.; Matteucci, F.; Di Iorio, V.; Paganelli, G.; Sarnelli, A.
Abstract : Purpose: Radiometabolic treatment with 177 Lu-PSMA (prostate-specific membrane-antigen) have shown to be a promising option for progressive prostate cancer patients with metastatic disease. Main organ toxicity limiting maximum injectable activity were kidneys(KDs), parotid glands(PGs) and red marrow(RM). We evaluated the delivered dose to healthy tissues(KDs, PGs, RM) for 177 Lu-PSMA treatments in combination with mannitol intra-venous infusion and iron mineral glutamate oral administration(via candy) combined with ice external application in order to reduce KDs and PGs uptake, respectively. Methods and materials: Six patients were enrolled (Table 1). Post injection whole body(WB) planar scans and blood samples were acquired at different timing (1 h, 16–24 h, 36–48 h, 120 h post-injection). ROIs for whole body, KDs and PGs were contoured on the first image and transferred to all others(Xeleris software, GE). KDs and PGs mean counts were normalized to initial whole body activity and (corrected for background, scatter, physical decay and patient's thickness) used to generate biological time-activity curves. Blood samples measurements (High-Purity Germanium detector) were used for RM uptake activity and biological time-activity curve estimation. Dose calculations in terms of mGy/MBq were performed following MIRD formalism(OLINDA/EXM software). Obtained results were compared to previous studies[1, 2] with unpaired T-test. Results: No statistically significant difference was found for whole body (median[range]:0.04[0.02–0.05] vs 0.05[0.01–0.10] mGy/MBq, p-value = 0.37) or RM (0.04[0.001–0.08] vs 0.03[0.01–0.06], p-value = 0.85) absorbed dose (Figure1). Absorbed dose to kidneys was lower for our patient cohort (0.20[0.11–0.31]) compared to data[1, 2](0.86[0.20–1.90]), with statistically significance (p-value = 0.001). Parotid glands absorbed dose was not statistically significant different considering all patients(0.79[0.33–1.24] vs 1.73[0.30–9.50], p-value = 0.24), but the difference increased considering only patients that received iron mineral candy administration (0.40[.33–0.47] vs 1.73[0.30–9.50], p-value = 0.09). Conclusions: The possibility to reduce kidneys and parotid gland absorbed dose in 177 Lu-PMSA treatments with the administration of combined therapies was shown. The increased of therapeutic index (i.e. same injected activity vs lower dose to main limiting healthy tissues) may provide the possibility to perform injected activity escalation of 177 Lu-radioisotope linked to PSMA, compared to previous ligand.